Identification of Some Potential Herbals with Anti-Mucorales (Antifungal) Properties: An Unholy Consortium between COVID-19 and Mucormycosis - Yepthomi, Tokika; Sharma, Sanjay; Khan, Arshad Alam; Salman , .; Mishra , Abhishek; Jain , Ashita (Perspective of Recent Advances in Medical Research Vol. 12, 2023)
The study aims to identify some potential herbals with anti-Mucorales (antifungal) properties. Antifungal and anti-Mucorales drugs are still scarce in the modern healthcare system's arsenal. This has led to a higher mortality rate in the affected population, particularly following the COVID-19 pandemic. Mucormycosis is a rare but serious fungal infection of the skin, sinuses, lungs, and brain, caused by a group of ubiquitously present molds called mucormycetes. Although its occurrence is sporadic, the manifestation can be life-threatening under several medical conditions and the associated risk factors. A comprehensive literature search was conducted across the PubMed database, LILACS, the Cochrane Register of Controlled Trials, Google Scholar and others using key words COVID-19, SARS CoV-2, Mucormycosis, Rhizopus, vaccine, steroids, antifungal drugs and herbals. Full texts of the retrieved articles published in English were accessed. A handful of medicinal plants such as Satureja khuzestanica Jamzad, Thymus danensis and Thymus carmanicus, Thymus vulgaris L, Lavandula angustifolia, Mentha piperita and some species of pepper such as Piper sp., Piper tuberculatum and P. hispidum have all shown to have a promising antifungal effect on Mucorales fungus. Extensive and intensified research should be carried out to identify further, design and develop new and safer antifungal drugs that can be powerful in treating mucormycosis.